Applicability of the social identity model of collective action in predicting support for interreligious violence in Indonesia. Issue 3 (26th December 2019) - Setiawan, Tery; Scheepers, Peer; Sterkens, Carl
Abstract : To what extent does religious identification promote collective efficacy and perceived injustice that contribute to explain support for interreligious violence in Indonesia? This overarching research question is inspired by theoretical insights starting from social identity theory, and noticeably enriched by collective action theories. We use high‐quality data of 1, 995 randomly selected individuals (Muslims and Christians) from across the Indonesian archipelago to investigate the mediating effects of perceived injustice and collective efficacy on the relationship between religiosity and support for interreligious violence. We also improve upon previous research with an elaborate measure of religiosity (beliefs, practice, and salience). Our structural equation modelling analysis reveals that collective efficacy significantly mediates the relationship between the religiosity dimensions and support for interreligious violence. Moreover, on average, the Muslim community has a higher level of collective efficacy, as compared to the Christian community, which positively affects the relationship between most religiosity dimensions and support for interreligious violence. An interesting finding is that in the Christian community, salience is overall negatively related to collective efficacy, which then negatively affects support for interreligious violence. These results provide novel empirical insights on the role of religious identity in interreligious conflicts in the South Asian context, especially Indonesia.